Development of Science Technology Engineering and Mathematics (STEM) Embedded Evaluation Tool for Micology Learning - Nurul Alfi Oetari; Idramsa Idramsa (Universitas Labuhanbatu, 2025)
Background: STEM learning can help students understand science concepts, improve science skills, create active, creative, motivating learning and provide opportunities for students to apply the material and build their knowledge. This research aims to develop valid and reliable science, technology, engineering and mathematics-based student evaluation tools on fungi material. Methodology: The evaluation instrument was developed using the 4D development model, which includes four stage: Define, Design, Develop and Determine. The study involved 30 first-grade students from MAS Madinatussalam, North Sumatra. The developed evaluation tool consisted of 40 questions. Validation by industry experts confirmed the instrument’s validity and reliability. Findings: Expert evaluations of the questions indicated high suitability, with an average score of 96.75%. Material experts rated the instrument with a suitability score of 92.5%, while media experts gave an average score of 86.1%, all falling within the